The dark flight down - Sedgwick, Marcus (London : Orion Children's Books, 2004)
On an errand for Kepler, his new master, Boy is captured and imprisoned in the palace dungeon, where he plots his escape from the evil Maxim and the lunatic King Frederick but also learns a disturbing secret about his father.
010 & up.
Keywords: Magic -- Fiction; Magicians -- Fiction; Identity -- Fiction; Kings, queens, rulers, etc. -- Fiction; Fathers -- Fiction; Horror stories